Spiritual Activity as an Effort to Cope with Depression during the COVID-19 Pandemic in Indonesia - Wurisastuti, Tri; Helda , Helda (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Spiritual activity is used to be associated with better mental health, particularly in the face of stress. At the beginning of the COVID-19 pandemic, numerous new regulations, including quarantine, restrictions on mobility, and physical distancing, triggered stress throughout society. The objective of the study is to explore the relationship of spiritual activities at each level of depression in Indonesia in the early stages of the COVID-19 pandemic (2-4 May 2020). The cross-sectional research was administered online in 34 provinces in Indonesia, involving 2189 respondents aged 15 years old and over and social media users. The researchers employed a structured questionnaire to examine demographic characteristics and coping activities and measured depressive symptoms using the Patient Health Questionnaire (PHQ-9). Multivariate results presented that the spiritual activities are able to decrease the risk of depression at every depression level (mild, moderate, and severe) after being controlled by gender and marital status. The values for each level, which are mild, moderate, and severe, were OR=0.332 (95% CI 0.19-0.60; p-value=0.000), OR=0.198 (95% CI 0.09-0.43; p-value=0.000), and OR=0.234 (95% CI 0.08-0.64; p-value=0.005), respectively. Good spiritual activities during an infectious disease outbreak are efficient to support some individuals in reducing the risk of depression, particularly in Indonesia.